The Influence Of Brand Image and Product Quality On Repurchase Intention Mediated by Customer Satisfaction In Maxx Coffee Customers - Tarigan, Riki Thomas; Sembiring, Beby Karina Fawzeea; Situmorang, Syafrizal Helmi (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This research aims to analyze the influence of Brand Image and Product Quality on Repurchase Intention which is mediated by Customer Satisfaction in Maxx Coffee Customers. This research involved 120 respondents selected using convenience sampling techniques. Data collection was carried out through a cross-sectional questionnaire or one shot study. The research instrument was tested for validity and reliability. Data analysis was carried out using verification analysis including multiple regression analysis and Sobel test. The research results show that Brand Image has a positive and significant effect on Customer Satisfaction, Product Quality has a positive and significant effect on Customer Satisfaction, Brand Image has no positive and significant effect on Repurchase Intention, Product Quality has a positive and significant effect on Repurchase Intention, Customer Satisfaction has a positive effect and significant on Repurchase Intention, and Customer Satisfaction does not mediate the influence of Brand Image and Product Quality on Repurchase Intention.